EXTH-53. IN VIVO QUANTITATIVE ANALYSIS OF ONCOLYTIC VIRUS-TUMOR KINETICS. (5th November 2018) - Ito, Hirotaka; Nakashima, Hiroshi; McLaughlin, Eric; Chiocca, E Antonio
Abstract: Oncolytic virus (OV) immunotherapy is becoming a clinically feasible therapy for cancer, with one FDA-approved product and many more in the clinical trial pipeline. Yet, there are still gaps in mechanistic knowledge related to how much oncolysis and OV replication is needed to achieve efficacious cytotoxic T cell responses. We have developed a series of "tools" to understand the kinetics of OV replication and correlate with antitumor efficacy. These consist of an oncolytic HSV that expresses two luciferase isoforms (Rluc and Fluc) activated at immediate early or late stages of viral replication cycle and U87dEGFR cells expressing a secreted luciferase (Cluc). Cluc levels in serum significantly correlated with tumor volumes measured by MRI ( r = 0.9653). U87dEGFR-Cluc tumors in the brains of athymic mice were treated with this oncolytic HSV. Temporal analyses of the OV and tumor luciferases clustered mice into those that responded to therapy as assayed by stable MRIs or did not (MRIs showing increasing tumor volumes). While there was no significant difference in maximum tumor infection level by OVs between responders vs. non-responders ( p = 0.17), responders showed significantly higher levels of replication ( p = 0.036), followed by significantly faster decrease in both OV and tumor-expressed luciferases ( p < 0.0001). Non-responders exhibited enlarging areas of tumor necrosis measured by T2 weighted MRI (increased from 10.3 to 17.4mm 3 on day12-16 compared to a decrease from 10.8 to 4.7mm 3 in responders) which correlated with the signal intensity of OV-expressed Rluc and Fluc ( r = 0.6807 and 0.5526, respectively). Histologically, responders showed an even biodistribution of OV in tumors with densely recruited Iba-1 positive cells while non-responders had uneven distribution sometimes with tumor hemorrhages (3/6 in non-responders, 0/2 in responders). These analyses can help us better understand the results of OV therapy from clinical trials.